Presencia de Harpasus quadrifolium González, Corrêa y Almeida,2008 (Coleoptera: Coccinellidae, Chilocorinae) en plantas de cocotero (Cocos nucifera L.) y naranja (Citrus sinensis (L.)), en Venezuela - Perozo, José; Cemeli, Mario; Camacho, Daniel (ENTOMOTROPICA, 2009)
Harpasus quadrifolium is reported from coconut and orange trees from the states of Amazonas and Aragua (Venezuela), feeding on Diaspididae scales, brown citrus aphid Toxoptera citricida and Asian citrus psyllid Diaphorina citri. This species was originally described from specimens at the Museum Klaus Raven Büller, Universidad Nacional Agraria La Molina Peru, from the Chanchamayo region